Downregulated KLK13 expression in bladder cancer highlights tumor aggressiveness and unfavorable patients' prognosis - Tokas, T.; Avgeris, M.; Alamanis, C.; Scorilas, A.; Stravodimos, K. G.; Constantinides, C.A. (J Cancer Res Clin Oncol, 2017)
PURPOSE: Despite recent research advantages on the molecular and subcellular background, bladder cancer (BlCa) remains a clinically neglected malignancy. This is strongly reflected by the generic approach of disease diagnosis and management. Additionally, patients' prognosis became a rather demanding task due to the great disease heterogeneity. Here, we aimed to evaluate, for the first time, the clinical value of KLK13 in BlCa. METHODS: A total of 279 bladder specimens (137 tumors, 107 adjacent normal tissues and 35 healthy samples) were included. Total RNA was extracted, reverse transcribed, and KLK13 expression was assessed by quantitative real-time PCR. RESULTS: KLK13 expression is significantly increased in bladder tumors compared to normal adjacent epithelium. However, reduced KLK13 expression is correlated with disease aggressiveness, including higher tumor stage and grade, and high-risk TaT1 tumors according to the EORTC stratification. Moreover, Kaplan-Meier and Cox regression analysis highlighted the prognostic value of the reduced KLK13 expression for the prediction of TaT1 patients' recurrence and shorter disease-free survival following TURBT. Finally, the combination of KLK13 expression with EORTC-risk stratification results to an improved prediction of TaT1 patients' outcome. CONCLUSION: This first clinical study of KLK13 in BlCa reveals its deregulated expression in bladder tumors and highlights KLK13 as a promising marker for improving TaT1 patients' prognosis following treatment.
Keywords: *Prognosis; Adult; Aged; Biomarkers, Tumor/biosynthesis/genetics; bladder tumors; Disease-Free Survival; Female; Gene Expression Regulation, Neoplastic; Humans; Kallikrein 13; Kallikrein-related peptidase 13; Kallikrein-related peptidases; Kallikreins/*biosynthesis/genetics; Kaplan-Meier Estimate; Klk; KLKs; Male; Middle Aged; Neoplasm Invasiveness/*genetics/pathology; Neoplasm Recurrence, Local/*genetics/pathology; Neoplasm Staging; RNA, Messenger/biosynthesis; Urinary Bladder Neoplasms/*diagnosis/genetics/pathology